The Relationship of Primipara's Post Partum Mother's Anxiety Level and Expenditure Breast Milk in The Postpartum Room at Rskd Mother and Child Siti Fatimah Makassar - Ekayanti, Ekayanti (ScieClouds Publishing, 2023)
Problem breast milk production by day First after give birth to can caused by a reduction stimulation hormone oxytocin . Anxiety that occurs during periods postnatally caused Because exists transition process in the process of becoming parent . Objective study is For connection level worry Mother post partum primipara with expenditure Breastfeeding in the Postpartum Room at RSKD Mother and Child Siti Fatimah Makassar. Type study This is non-experimental research with analytical methods , using a cross-sectional design . Population in study This is the average number of post mothers partum primiparas within one month who were cared for in the Postpartum Room at RSKD Mother and Child Siti Fatimah Makassar , namely 38 people . Sample studied _ is post mom partum primipara as much 34 people use technique accidental sampling , which was carried out starting date 11 to 17 April 2016. Data collected with questionnaire Then done analysis statistics using the chi square test with alternative tests Fisher 's exact test with levels meaning a < 0.05. The research results showed that of the 34 respondents studied, the majority of respondents did not experience anxiety, namely 22 people (64.7%) and the majority of respondents with smooth breast milk production, namely 24 people ( 70.6 % ). Based on results study concluded that there is a relationship level worry Mother post partum primipara with breast milk production , with p value = 0.00 1 < 0.05 . Recommended for institutional institutions Service , expected For can provide counseling to primiparous mother about method maintenance baby and way correct breastfeeding , so that mothers know more about the breastfeeding process and the factors that cause breast milk to not flow smoothly.